Persepsi Mahasiswa terhadap Penggunaan Aplikasi Canva dalam Pembelajaran Menulis di Perguruan Tinggi. - Satriani, Intan; Fauziah, Ula Nisa El (Kopertis Region IV Jabar and Banten, 2026)
This study aims to investigate university students’ perceptions of using the Canva graphic design application as a learning medium in an English writing class. The study employed a qualitative descriptive design. The participants were thirty fifth-semester students enrolled in a Professional Writing course at a private university in Cimahi, West Java. Data were collected through a questionnaire adapted from Utami et al. (2021), which focused on three indicators: perceived usefulness, ease of use, and suitability in supporting writing skills. The findings indicate that most students perceived Canva as a useful and engaging tool that supports the development of their writing skills, particularly in terms of increasing motivation, enhancing confidence, and improving information recall. The results suggest that integrating Canva into writing instruction can provide pedagogical benefits and create a more supportive and motivating learning environment for university students. Keywords: Canva Application, Students’ perceptions, Writing Skills